‘And he sent them in pairs’ (Luke 10:1): Reimagining mission in Africa as a response to the Synodal Process - Mensah, Michael Kodzo (Missiology, 2025)
The Catholic Church’s current Synod on synodality identifies mission as one of the key areas in which the entire church needs to ‘walk together’. In Ghana for example, the 2021 Population and Housing Census revealed an alarmingly sluggish growth of Catholic Church which has been viewed as a call to the local church to reexamine its mission strategy. The Lucan account of the mission of the seventy-two (Lk 10:1-12) is particularly relevant to this conversation. Mission in this passage is focused on three dimensions: The agents who are sent out in pairs; the household (οἰκία/οἶκος), the primary locus for the mission; and the city (πόλις), which could either be receptive to or reject the message. Using the evaluative approach of African Biblical Hermeneutics, this study attempts to assess the current state of the Catholic Church’s mission in Ghana considering the Lucan paradigm while drawing out the implications for Catholic evangelization in contemporary Africa.